The commitment of sheep and goat production systems in the agro – ecological transition: a collective participative approach in Corsica - Dubeuf J.-P.; Casabianca F. (Innovation for sustainability in sheep and goats, 2019)
The importance of environmental challenges in agriculture and livestock production requires an ecological transition of the production systems including the sheep and goat ones. In this context, establishing the conditions for agro–ecological changes and building innovative pathways of changes could favor this transition. After a presentation of some theoretical concepts behind the idea of ecological transition and agro – ecology, the objective of this communication is to report the implementation of a participative approach involving scientists, technicians, teachers and breeders in Corsica Island focusing on pastoral systems. This approach aims to design the performances of the systems from their triple social economic and environmental dimensions, how they are in line with the agro – ecological orientations and how to improve them. Inspired from previous methodologies but innovating through a participative approach, an easy-to-implement method has been adjusted to the characteristics of the local systems and agro-ecological criteria for sheep and goat herds and systems, we designed 10 groups of indicators including societal dimensions integrated in an Agroecological Livestock Proximity Index (ALPI). The exchanges during the sessions have shown that agro-ecology is not only an institutional injunction. It is also a collective methodological approach and pathway to design which innovations could support the sustainable development and changes in sheep and goat farming and specially, in pastoral systems. The utilization of this method and its further developments are evoked.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)